Lady jane grey or queen kateryn parr? National portrait gallery painting 6804: Analysis and historical context - Susan E. James (Cogent Arts & Humanities, 2018)
In October 2006, the National Portrait Gallery in London acquired a late sixteenth-century, three-quarters length panel portrait of a woman, NPG 6804, and concluded that this work was a copy taken from an original likeness of the elusive Lady Jane Grey (c.1537–1554), portraying her in 1553 during her brief reign as nine-day queen. Since then new historical research has been published which throws doubt on both this identification and on the dating of the original source image and supports an alternative identification—that of Kateryn Parr (c.1512–1548), sixth queen of Henry VIII. Although undoubtedly NPG 6804 was intended for sale as a portrait of Jane Grey, recent findings suggest that it is instead a copy of an original image of Kateryn Parr painted in the summer of 1544 at Hampton Court, possibly by a painter named John Hayes. The first goal of this article is to analyze these new findings and the ways in which they challenge previous conclusions. The second goal is to suggest the reasons for which the original portrait may have been commissioned. Toward these goals, the discussion undertakes to put the source painting and its purpose in an historical context and together with an examination of the indicators internal to the portrait apply them in support of this proposed alternative identification.